Dynamika i kierunki zmian aktywności gospodarczej mieszkańców obszarów wiejskich - Brodzińska, Katarzyna (Indices and Directions of Rural People Economic Activity Change in Rural Areas, 2006)
The purpose of the research is to learn about the indices and directions of rural people economic activity change in rural areas. The resources were conducted in years 2000-2004. Statistics data of rural people enterprises number came from the Main Statisticall Office (GUS). The obtained results enabled to establish the rural people economic activity direction changes in rural areas in particular economic sectors (agriculture, industrial and market services).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 116-121